Perilaku Keuangan Gen Z dalam Penggunaan Qris: Studi Kasus Mahasiswa Ekonomi dan Bisnis Universitas Mataram - Novia Fitriani; Herlina Pusparini (Studia Economica : Jurnal Ekonomi Islam, 2026)
This study aims to analyze the financial behavior of Gen Z in the use of Quick Response Indonesia Standard (QRIS) among students of the Faculty of Economics and Business, University of Mataram. The research method used was quantitative with a population of 3,070 active students from three undergraduate study programs: Accounting, Development Economics, and Management. The research sample was calculated using the Slovin formula and rounded up to 354 respondents. The results showed that the majority of students of the Faculty of Economics and Business, University of Mataram have adaptive and pragmatic financial behavior through the use of QRIS. Students from the three study programs, namely Accounting, Development Economics, and Management, showed a high level of acceptance with very low resistance. Development Economics students showed the most superior response compared to other majors, reflecting a higher readiness and enthusiasm in adopting digital technology to manage daily financial transactions. This finding is in line with the characteristics of Generation Z who quickly adapt to technological innovation and the digitalization of financial transactions. The positive acceptance of students indicates that the use of QRIS can be promoted more widely as an efficient, secure, and practical digital payment method. In addition, the results of this study serve as a basis for universities and digital service providers to design socialization programs and implementation strategies that support modern, adaptive, and efficient student financial behavior